PENERAPAN APLIKASI SISTEM KEUANGAN DESA (SISKEUDES) DALAM MENINGKATKAN KINERJA APARATUR DESA DI KECAMATAN LUBUK RAJA - Anis Feblin; Chefi Rizky Djuliar (KOLEGIAL, 2021)
Making village fund financial reports using the manual system often makes mistakes and mismatches of the results of the details of these funds, using the manual system requires accumulation of paper and a lot of waste of village budgets in Lubuk Raja District. Therefore, the central government and the BPKP (Financial and Development Supervisory Agency) made a regulation that the ten villages in Lubuk Raja District had to apply the village financial system application for the production of village financial reports. The research objective was to determine the application of village financial system applications in improving the performance of village officials in Lubuk Raja District. The method used in this research is descriptive comparative with qualitative analysis, the research uses primary data sources with research techniques such as interviews, observation, and documentation. The results showed that the implementation of the village financial system in terms of quality, quality, responsibility, cooperation, and initiative was in a fairly good category so that seen from the performance of the village apparatus it had increased. The application of the village financial system application in village financial management is more transparent and accountable, so that better governance is created.